Monitoring by Raman spectroscopy of the damage induced in the wake of energetic ions. (15th May 2014) - Miro, Sandrine; Velisa, Gihan; Thomé, Lionel; Trocellier, Patrick; Serruys, Yves; Debelle, Aurélien; Garrido, Frédérico
<x xml:space="preserve">Abstract</x> This article reports micro‐Raman experiments performed on cross sections of 6H‐SiC crystals irradiated with heavy ions of different energies. The results demonstrate that this technique is very powerful to quantify the damage created in the wake of energetic ions from the surface of samples down to the ion resting position. For slow ions (900‐keV I), ballistic collisions lead to the amorphization of the surface region of samples. For swift ions (36‐MeV W), the surface region remains crystalline and amorphization occurs around the end of the ion path. Moreover, synergistic effects between electronic and nuclear slowing down processes are put forward. The methodology used in this work may be adapted to other materials where radiation effects need to be investigated, provided that the damage created by irradiation is detectable by Raman spectroscopy. Copyright © 2014 John Wiley & Sons, Ltd.